Role of vitamin D and calcium in the relief of primary dysmenorrhea: a systematic review - Abdi, Fatemeh (Obstet Gynecol Sci, 2021)
Dysmenorrhea is one of the well-established problems among women of reproductive age and can have adverse effects on the quality of life of the individual. Some studies suggest a relationship between vitamin D (Vit D) and calcium deficiency and the emergence of early dysmenorrhea. Accordingly, a systematic study was performed to investigate the role of calcium and Vit D in the relief of primary dysmenorrhea. A systematic literature search was performed in PubMed, Web of Science, Scopus, Science Direct, and Google Scholar for papers published between 2010 and 2020. The Consolidated Standards of Reporting Trials and Strengthening the Reporting of Observational Studies in Epidemiology checklists were used to assess the quality of the studies. The risk of bias was assessed using the Cochrane risk-of-bias assessment tool. Low calcium levels lead to an increase in uterine muscle contraction and can cause pain after decreased uterine blood flow. Furthermore, low levels of Vit D can increase primary dysmenorrhea by increasing prostaglandin production or reducing intestinal calcium absorption. That being the case, Vit D and calcium intake can be effective in reducing the severity of primary dysmenorrhea and in reducing the rate of analgesic use. Low levels of Vit D and calcium are inversely related to the severity of primary dysmenorrhea, and Vit D and calcium intake can reduce the severity of primary dysmenorrhea and its associated systemic symptoms. Therefore, the use of calcium and Vit D supplements can be recommended to relieve dysmenorrhea.